Impact of Monetary Policy on Small Scale Enterprises Financing in Nigeria - Kolawole, Ebire (International Journal of Small and Medium Enterprises, 2018)
Small and Medium Scale Enterprises play vital roles in the economy which are usually instrumental in achieving macroeconomic goals. This has attracted the attention of monetary authorities to institute policiesto boostconducive environment for SMEs to thrive. This study therefore empirically investigates the impact of monetary policy on SMEs financing in Nigeria spanning from the first quarter of 1992 to the last quarter of 2016. The time series data were subjected to unit root test to ascertain the stationarity of the variables and thereafter, cointegration and Error Correction Model (ECM) technique were used for the analysis. The residuals of the analysis were further subjected to various diagnostics tests. The result revealed that interest rate has a positive and significant impact on the SMEs financing in Nigeria. On the other hand, inflation rate was found to have a significant but negative impact on SMEs financing in Nigeria. Money supply and exchange rate were found to be insignificant in impactingSMEs financing. Based on this finding, the study recommends that, monetary authorities should give special attention to SMEs in specific sectors by creating special windows through various financial institutions to grant low interest rate so as to grant SMEs access to funds.This will boost business growth and consequently achieve macroeconomic goals.